Letter of condolence to Max Bredig, April 26, 1944 (1944)
Letter of condolence regarding the death of Georg Bredig (1868-1944) from "DSM" to Max Albert Bredig (1902-1977).
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Condolence notes